Advancing Industrial Relations Theory: An Analytical Synthesis of British-American and Pluralist-Radical Ideas - Kaufman, Bruce; Gall, Gregor (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2015)
SummaryProminent writers in industrial relations (IR) have concluded the field is in significant decline, partly because of a failed theory base. The theory problem is deepened because other writers conclude developing a theory foundation for industrial relations is neither possible nor desirable. We believe advancing IR theory is both needed and possible, and take up the challenge in this paper.A long-standing problem in theorizing industrial relations has been the lack of agreement on the field’s core analytical construct. However, in the last two decades writers have increasingly agreed the field is centred on the employment relationship. Another long-standing problem is that writers have theorized industrial relations using different theoretical frames of reference, including pluralist and radical-Marxist; different disciplinary perspectives, such as economics, sociology, history, and politics; and from different national traditions, such as British, French, and American.In this paper, we seek to advance IR theory and better integrate paradigms and national traditions. We do this by developing an analytical explanation for four core features of the employment relationship—generation of an economic surplus, cooperation-conflict dialectic, indeterminate nature of the employment contract, and asymmetric authority and power in the firm—using an integrative mix of ideas and concepts from the pluralist and radical-Marxist streams presented in a multi-part diagram constructed with marginalist tools from conventional economics. The diagram includes central IR system components, such as labour market, hierarchical firm, macro-economy, and nation state government. The model is used to explain the four features of the employment relationship and derive implications for IR theory and practice. Examples include the diagrammatic representation of the size and distribution of the economic surplus, a new analytical representation of labour exploitation, identification of labour supply conditions that encourage, respectively, cooperation versus conflict, and demonstration of how inequality of bargaining power in labour markets contributes to macroeconomic stagnation and unemployment.